The Development of an Algorithm to Determine Axial Capacity of Piles from SPT N-Values - Ambrose, Jasmin (2000)
An algorithm was developed to determine axial capacity of piles in sand and clay. The standard static formulae to determine pile mcapacity in clay were selected (a-API, A, SEMP and RAND) and the calculated capacities were calibrated using measured results to produce prediction formulae. For capacity prediction in sand, comparison of results using other methods (Davisson and Chin's formulae) were selected and recalibrated according to the iterative technique (IT). The combined calibrated formulae (The Algorithm) were later tested using five static loading test results. The comparison between measured and predicted capacities was conducted using standard deviation values to determine the amount of error in the prediction. Final analysis showed that a combination of capacity prediction formulae calibrated from Davisson's failure criterion for piles in sand and America Petroleum Institute formula for piles in clay, [O]+[APIJ, compared to measured capacity from Butler & Hoy failure criterion was the most consistent algorithm . Another comparison between measured capacity from Pile Dynamic Analyzer (PDA), predicted capacity using [D]+[API) and calculated capacities from iterative technique for piles in sand and clay [IT]+[IT] was conducted. Results indicate that {IT]+[IT] is more consistent with PDA analyzer results than [O]+[API1 results. In the search to determine a consistent yet suitable and advanced method of determining pile capacity, an iterative technique was also developed whereby IT has long been used in numerical analysis for microcomputers (engineering software). The developed IT was used for all cases of algorithm testing. It is speculated that better correlation values can be obtained if more loading test data are available during the course of this study.